Preterm Delivery and Low Birth Weight: A Study on Teenage Mothers in Bangladesh (Bangladesh Medical Journal, 2026)
Despite legal restrictions on early marriage, teenage pregnancy remains highly prevalent in Bangladesh and is associated with adverse maternal and neonatal outcomes. Low birth weight (LBW) and preterm birth are major contributors to neonatal morbidity and mortality. This study aimed to determine the proportion of preterm delivery and LBW among teenage mothers and to describe associated sociodemographic and obstetric factors. This cross-sectional study was conducted from June 2021 to March 2024 in the Department of Obstetrics and Gynecology at Dhaka Medical College Hospital. A total of 85 pregnant adolescents aged 16–19 years were enrolled using predefined criteria. Data were collected using a semi-structured questionnaire that covered sociodemographic characteristics, reproductive history, obstetric complications, and neonatal outcomes. Preterm birth was defined as delivery before 37 completed weeks, and LBW as birth weight